The Essential Guide to HTML5 Using Games to Learn HTML5 and JavaScript - Meyer, Jeanine (Apress, 2018)
Gain a deep, practical knowledge of HTML and JavaScript that will provide an introduction to programming and enable you to build interactive websites. This completely updated second edition explains HTML, JavaScript and CSS in the context of working examples and contains full-color screen shots of the programs in action. You'll begin at an introductory level, learning the essentials of HTML5 and JavaScript and programming techniques. Each chapter features either a familiar game such as Hangman, Rock-Paper-Scissors, Craps, Memory, and Blackjack, or a simple type of game, such as a quiz, a maze, or animated simulations. You'll develop solid programming skills that will help when learning other programming languages. Each chapter contains tables revealing the structure of the program with comments for each line of code. These examples demonstrate the features introduced with HTML5. You'll see how to use canvas elements for line drawing. You can include your own audio and video clips, directly controlled by your JavaScript code. For example, the reward for correct completion of a quiz can be the playing of an audio clip and a video clip. You'll also learn how to use localStorage to store high scores or game preferences on a user's computer for retrieval next time they play. The Essential Guide to HTML5 explores all of this and more.